Mengoptimalkan Literasi Pajak Generasi Z Melalui Platform Coretax - Gjosphink Putra Umar Sakka; Muhammad Arfan; Arga Wiradarma; Irfan Irfan; Omasrianto Omasrianto (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
The digital transformation of tax administration in Indonesia through the implementation of Coretax necessitates improved tax literacy among the public, particularly Generation Z, a productive age group that is highly familiar with digital technologies. However, Generation Z's proximity to technology does not necessarily correspond to an adequate understanding of tax obligations, tax administration procedures, and the utilization of digital tax services. This community engagement program aims to enhance Generation Z's understanding of taxation through Coretax socialization using an educational and participatory approach. The socialization materials covered fundamental taxation concepts, the role of taxation in national development, taxpayers' rights and obligations, an introduction to Coretax, and the workflow of digital tax administration services. The results indicate an improvement in participants' understanding of tax functions, the importance of tax compliance, and the benefits of Coretax as a digital tax administration platform. This initiative highlights the importance of continuously developing technology-based tax education programs to ensure that Generation Z not only becomes active digital technology users but also evolves into tax-aware, compliant, and responsible future taxpayers.